A A RESOURCE ALLOCATION PROBLEM IN HIGHER EDUCATION WITH INTEGRATED MULTICRITERIA DECISION MAKING - dame ifa sihombing; Lamtiur Sinambela; Labuan Nababan (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2020)
This paper analyzes forms of resource allocation problems in higher education. Resource allocation is one of the major decision problems arising in higher education. Resources must be allocated optimally is such a way that performance of universities can be improved. It combines two of the most extended multicriteria decision making techniques: the Analytic Hierarchy Process (AHP) and Goal Programming (GP). The AHP approach is used in evaluation all criteria such as qualitative and quantitative factors. Then the Goal Programming (GP) model incorporating the constraints to select the best set of all goals without exceeding the limited avalaible resources. In this paper two commercial packages are used : Expert Choice for determining the AHP priority ranking of the projects, and LINGO 17 for solving the GP model.